2007
DOI: 10.1038/sj.mt.6300026
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System-directed AAV2/5-Mediated Gene Therapy Synergizes with Bone Marrow Transplantation in the Murine Model of Globoid-cell Leukodystrophy

Abstract: Globoid-cell leukodystrophy (GLD) is a rapidly progressing inherited neurodegenerative disorder caused by a deficiency in galactosylceramidase activity. Previous studies in the murine model of GLD (Twitcher mouse) have shown that both bone marrow transplantation (BMT) and central nervous system (CNS)-directed gene therapy can be moderately effective at ameliorating certain aspects of GLD. As BMT and CNS-directed gene therapy target fundamentally different tissues, we tested the hypothesis that combining these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(118 citation statements)
references
References 30 publications
7
109
2
Order By: Relevance
“…As previously reported, an increased number of CD68-positive macrophages and activated microglia are found in the brains of Twitcher mice compared with WT controls at 36 d (Lin et al, 2007;Reddy et al, 2011). Triple treatment dramatically decreased CD68 staining at 36 d (Fig.…”
Section: Microglial and Astrocyte Activationsupporting
confidence: 62%
See 3 more Smart Citations
“…As previously reported, an increased number of CD68-positive macrophages and activated microglia are found in the brains of Twitcher mice compared with WT controls at 36 d (Lin et al, 2007;Reddy et al, 2011). Triple treatment dramatically decreased CD68 staining at 36 d (Fig.…”
Section: Microglial and Astrocyte Activationsupporting
confidence: 62%
“…1 top left). We previously showed that BMT or CNS-directed AAV-mediated gene therapy initiated in newborn Twitcher mice increased the median life span to ϳ45 and ϳ70 d, respectively (Lin et al, 2007;Reddy et al, 2011). In the current study, the median lifespan for mice treated with L-cycloserine alone or L-cycloserine plus CNS-directed gene therapy is ϳ57 and ϳ70 d, respectively.…”
Section: Lifespanmentioning
confidence: 99%
See 2 more Smart Citations
“…Improvements in the accelerating rotor-rod test were also evident in Twitcher mice, a model of globoid-cell leukodystrophy, transplanted at 3 days of age (4 Gy; 1 Â 10 6 donor cells), Fig. 2 (continued) despite brain galactosylceramidase activity not being significantly increased following treatment (Lin et al 2007). Twitcher mice transplanted at 8-11 days of age (9 Gy; 3-5 Â 10 7 donor cells delivered intraperitoneally) generated up to 15% normal levels of galactosylceramidase activity in the brain, which was sufficient to prevent hindlimb paralysis (Hoogerbrugge et al 1988).…”
Section: Discussionmentioning
confidence: 99%